Management and treatment patterns of diabetes patients having blood pressure complications living in Dhaka city, Bangladesh - Rahman, AHM Mahmudur; Saran, Lutful Haque; Rashid, Md Mamun Ur; Taher, Adnan (Asian Journal of Medical and Biological Research, 2016)
A study way carried out in Dhaka city to find out the management and treatment patterns of diabetic patients those having blood pressure complications. It was a cross sectional study of 150 patients by using self administered survey questionnaire and founded data was analyzed and described. In this study, it is found that almost all of the patients (92%) were from Dhaka and just were a few those were outsider but came as referred patients. The male and female percentages were accordingly 64.67% and 35.33% and among those diabetes patients 47.33% had hypertension and 10.66% had hypotension and most of them (74%) check their diabetes monthly. Among those patients 79.33% patients were prescribed only drugs while 17% patients were prescribed to change their routine only and 4% were prescribed both (drug and routine). Most of the diabetes patients having blood pressure complicacy were prescribed only drugs which is very significant and those are going to do further research in this aspect will be benefited by getting this information. Asian J. Med. Biol. Res. September 2016, 2(3): 458-463